The Automation of Standard People Operations in the Energy Transport - Зиновиев, Владимир; Николов, Николай (Научни трудове, 2021)
The automation of business processes and operations is a global trend. Automation is software or mechanical self-fulfilling process without or with a minimal human intervention and control. In specific processes and parts of the energy transport the automation is already happening. It can replace significant part of human labour or just to take and reduce the routine physical or repeating mental efforts of the jobs. Automation tools and systems in the energy transport are strongly dominated by open-source software automation tools. Therefore, a part of professional skills required before automation will not be useful in the future, but to handle automation trend, many new skills and knowledge will be needed by the human jobs of the future.
Keywords: Автоматизация; Отворен код; Софтуер; Енергиен транспорт; Умения; Труд; Tехнология; Алгоритъм; Работа; Изкуствен интелект (ИИ)